REKONSTRUKSI NALAR PERADABAN ISLAM - Rusli, Muh. (ULUL ALBAB Jurnal Studi Islam, 2012)
Islam has enriched the glorious time in its early civilization period. However, it undergoes a set back later due to the wrong understanding of Muslims to their religion. Therefore, it is necessary to reconstruct the logic of Islamic civilization to regain the gloriousness. Among those required efforts are such as to create a new spirit toward a new civilization, the will to adopt new knowledges without problematizing its sources, reconstructing the meaning of â€œGodâ€™s free willâ€, on being â€œtolerant ummahâ€ and any efforts to strentheng the ummah.